The method of a-level of nominalization for intrusion detection systems - Корченко, Анна Александровна (Ukrainian Information Security Research Journal, 2015)
Modern facalities which are used for cyber attacks detec-tion in low defined partially formalized environment have a number of limitations. As part of this goal, the appro-priate technical solutions are developed for intrusion detection systems, where the basis is the method for anomalies detection caused by cyber attacks in infor-mation system. In this method the process of transfor-mation of standards and current fuzzy numbers requires the precise formalization. To overcome this limitation, a method which is based on mathematical models and methods of fuzzy logic and is implemented through three basic stages: formation of a-levels which is equivalent to the conversion of fuzzy numbers, the formation of ge-nerelized tables and graphical interpretation of nominal-ized fuzzy numbers. The method enables to formalize the process of -level intervals formation to get the equiva-lent transformation of standard and current fuzzy num-bers, which in turn will make it possible to define the identifying terms that indicate the current state of the environment and increase the efficiency of corresponding intrusion detection systems.